Effects of man-made fires on wetlands of the Paraná river in Argentina: perspectives of ecological restoration - Peltzer, Paola (2023)
Fire caused by man in South America is one of the most concerning environmental catastrophes, due to its potential impacts on global climate change. The aim of the present study was to determine the immediate effects of man-made fires on both the soil and the diversity of vascular plants and vertebrates present in the wetlands of the Paraná River (Argentina) during 2020, with emphasis on the perspectives of restoration in the short-term. In particular, we measured the depth of burning and listed the vascular plant and vertebrate species that were burned. We also collected field data of plant species by in situ observation (affected species, vegetal configuration, flam height on wood) and data on vertebrate species by visual encounter surveys. Species that could not be determined in situ were recorded by photographs for later identification in the laboratory. We also determined the difference normalized burn ratio (dNBR) and the normalized difference vegetation index (NDVI) before and after the fire event. The soil burned at a depth of 2-12 cm, whereas the flame heights ranged from 2.70 to 4.20 m due to the presence of woody species. At least, total of 46 plant and 39 vertebrate species were affected by fires. The dNBR index showed moderate (17.64%) to high (52.94%) burn severity. The NDVI values decreased by half compared to the values recorded in the control images immediately after the fire and showed low medium-term revegetation after three to four months. Since man-made fires in wetlands are likely to increase due to climate change in the coming years, there is an urgent need for legislation to regulate the conservation and restoration of these ecosystems.